Effect of the common AYUSH Yoga protocol in the management of Dyslipidemia: A clinical study - Bora, Manju; Arya, Jaideep (International Research Journal of Ayurveda & Yoga, 2023)
The present study was undertaken with a view to evaluating the effect of common Ayush Yoga protocol in the management of Dyslipidemia patients. A study was conducted on a clinical experimental basis. The interventional module used the common Ayush Yoga protocol which has a different form of Yogic practice, such as Yogasanas, Pranayama, Dhyana, etc. Interestingly, it is assumed that different Yogic practices have a different impact on physiological and psychological variables. This research aimed to find out the effect of common Ayush Yoga protocol practices on Dyslipidemia patients. Sixty (60) sample were selected for the Haryana region dist. Bhiwani only. The primary data for investigation were derived from clinical reports and personal observations. They were divided into two groups of 30 – 30 sample people. Group I served as the Yoga intervention group, and Group II as the control group. Common Ayush Yoga protocol practices were given to an experimental or interventional group only and the control group was not given any exposure and was kept under control. Initial and final data records were collected and statistically analyzed using the pre-post ‘t-test’. Results showed that common Ayush Yoga protocol treatment has prevention in the condition of Dyslipidemia patients.